Sulfuric Acid Treatment of Sapphire Substrates for Growth of High-Quality Epilayers - 최지원; 정연식; 윤석진; 김태환; Young-Soo No; Won-Kook Kim (한국세라믹학회, 2004)
The chemical etching of sapphire substrates was performed to produce smooth surfaces on an atomic scale. The sapphire surface etched by using a H2SO4 solution showed a pit-free morphology and was very smooth as much as rms=0.13 nm, that etched by using a mixture of H2SO4 and H3PO4 contained large pits with rms=0.34 nm. The rmss and the number of the pits increased with increasing etching temperature. The sapphire etched by using H2SO4 at 320℃ had the best surface. These results provide important information on the effects of etching treatment on the structural properties of sapphire for the growth of high-quality epilayers.